2020
DOI: 10.1371/journal.pone.0228510
|View full text |Cite
|
Sign up to set email alerts
|

Neurons from human mesenchymal stem cells display both spontaneous and stimuli responsive activity

Abstract: Mesenchymal stem cells have the ability to transdifferentiate into neurons and therefore one of the potential adult stem cell source for neuronal tissue regeneration applications and understanding neurodevelopmental processes. In many studies on human mesenchymal stem cell (hMSC) derived neurons, success in neuronal differentiation was limited to neuronal protein expressions which is not statisfactory in terms of neuronal activity. Established neuronal networks seen in culture have to be investigated in terms … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 55 publications
(63 reference statements)
1
9
0
Order By: Relevance
“…Both neuronal proteins were expressed in differentiated hMSCs (Figure 1C). The data were correlated with our previous findings in hMd-Neurons (43). To investigate apoptosis, caspase-3 activity was measured in neuronal induced cells, as caspase-3 is involved in the downstream signaling of the apoptotic cascade.…”
Section: Human Mesenchymal Stem Cells (Hmscs) Differentiated Into Viable Neurons In Vitrosupporting
confidence: 85%
See 3 more Smart Citations
“…Both neuronal proteins were expressed in differentiated hMSCs (Figure 1C). The data were correlated with our previous findings in hMd-Neurons (43). To investigate apoptosis, caspase-3 activity was measured in neuronal induced cells, as caspase-3 is involved in the downstream signaling of the apoptotic cascade.…”
Section: Human Mesenchymal Stem Cells (Hmscs) Differentiated Into Viable Neurons In Vitrosupporting
confidence: 85%
“…Considering previously suggested cellular dynamics regulated by integrin α5β1, in this study, involvement of integrin α5β1 in neuronal differentiation of hMSCs was examined based on a differentiation protocol we previously reported (43). The results showed that cytokine based induction of hMSCs into hMd-Neurons requires integrin α5β1 surface localization at specific time points (around day 5), while translocation into the cytosol was observed during further maturation.…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…However the cells were negative for hematopoietic lineage marker CD34. These results indicated that the isolated cells in this study represented HUCB-MSCs and were not mixed with cells of hematopoietic origin (Fig., 5,6,7).…”
Section: Immunophenotypic Analysis Of Mesenchymal Stem Cells In Vitromentioning
confidence: 55%